The course of diabetic retinopathy following cataract surgery in eyes previously treated by laser photocoagulation. Issue 4 (April 1992) - Pollack, A.; Leiba, H.; Bukelman, A.; Abrahami, S.; Oliver, M.
Abstract : The course of diabetic retinopathy following extracapsular cataract extraction with posterior chamber lens implantation in eyes previously treated by laser photocoagulation for diabetic retinopathy was retrospectively studied in 33 eyes (33 patients). In 20 eyes (61%) there was no change in the retinal status postoperatively. In 13 (39%) there was postoperative progression of diabetic retinopathy compared with the fellow non-operated eye, in which progression occurred in nine eyes (27%). The severity of the preoperative status affected the incidence of progression. Four eyes (12%) developed complications of diabetic retinopathy–that is, rubeosis iridis and vitreous haemorrhage–which regressed after lasering. Cystoid macular oedema developed in 13 eyes (39%) and its incidence varied according to the postoperative course of diabetic retinopathy. The majority of the eyes showed a postoperative improvement in vision.